Fabrication and characterization of a novel nanofiltration membrane by the interfacial polymerization of 1, 4-diaminocyclohexane (DCH) and trimesoyl chloride (TMC). Issue 51 (5th May 2015) - Chen, Gui-E.; Liu, Yan-Jun; Xu, Zhen-Liang; Tang, Yong-Jian; Huang, Hui-Hong; Sun, Li
Abstract : A novel thin-film composite polyamide membrane for nanofiltration is prepared, and the addition of sodium N -cyclohexylsulfamate is found to have a significant influence on its performance. Abstract : This study focuses on the preparation and nanofiltration properties of a novel thin-film composite polyamide membrane formed by the interfacial polymerization of 1, 4-diaminocyclohexane (DCH) and trimesoyl chloride (TMC) on a porous polysulfone supporting membrane. At the same time, we found that the introduction of sodium N -cyclohexylsulfamate (SCHS) can improve to a degree the water flux and salt rejection. The active surface of the membrane was characterized by employing SEM and AFM. The performance of the nanofiltration membrane was optimized by considering the preparation conditions, including the monomer concentration, reaction time, curing conditions and SCHS concentration. The resulting NF membrane prepared under the optimum conditions exhibited a Na2 SO4 rejection of 98.1% and a water flux of 44.6 L m −2 h −1 at 0.6 MPa. The pore size of the NF membrane was about 0.33–0.42 nm, which was calculated from the rejection of PEG and carbohydrates, respectively.